Effects of Lidocaine Injection at Acupuncture Points on Perioperative Analgesia in Cats Undergoing Ovariohysterectomy - Camila Menossi Sueza Lima; Camila Zanetti Segatto; Gustavo Ricci Zanelli; Gabriel Montoro Nicácio; Renata Navarro Cassu (Medical Association of Pharmacopuncture Institute, 2022)
Background : Pharmacopuncture is an acupuncture-related technique that has been used to amplify the therapeutic effects of different medications. Objectives: To investigate the analgesic efficacy of a lidocaine injection at acupoints in cats undergoing ovariohysterectomy. Methods : Thirty cats were randomly distributed into two groups (n = 15, per group). The experimental group received a bilateral administration of lidocaine at the following acupoints: Stomach 36 (ST-36) and Spleen 6 (SP-6) (Lido group). The control group did not receive lidocaine (Control group). All cats were sedated with dexmedetomidine and anesthesia was induced with propofol and maintained with isoflurane. Intraoperatively, fentanyl was given to control cardiovascular responses to surgical stimulation. Postoperative pain was assessed at various time points, up to 24 hours after extubation, using the UNESP-Botucatu multidimensional composite pain scale (MCPS) and Glasgow feline composite measure pain scale (CMPS-Feline). Sedation scores were measured at the same time points. Morphine/meloxicam was administered as rescue analgesia. Data were analyzed using t-tests, Fisher´s exact test, the Mann-Whitney test, and the Friedman test (p < 0.05). Results : Intraoperatively, more cats in the Control group required analgesic supplementation than those in the Lido group, but the difference was not significant (p = 0.65). Postoperative pain, sedation scores, and analgesic requirements did not differ between groups. Rescue analgesia was given to 67% (10/15) of the cats in each group. Conclusion : The administration of lidocaine at ST-36 and SP-6 acupuncture points did not provide significant perioperative analgesic benefits in healthy cats undergoing ovariohysterectomy.